PENGARUH AFFILIATE MARKETING DAN PROMO "TANGGAL-TANGGAL ISTIMEWA" TERHADAP KEPUTUSAN PEMBELIAN PADA E-COMMERCE SHOPEE(Studi Pada Mahasiswa Kota Medan) - Windi Ayu Ningrum; Ainun Mardhiyah (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2024)
The high interest in online shopping in the community has made many new e-commerce pop up in Indonesia, one of which is Shopee. The Shopee Affiliate program helps consumers to get direct product reviews. The "special dates" promo program gives the impression to consumers to buy products on these dates because they get cheaper prices. These two things are some of the considerations for consumers to make purchases at Shopee. This study aims to analyze the effect of affiliate marketing and "special dates" promos on purchasing decisions for students who use the Shopee application in Medan City. The influence between affiliate marketing and "special dates" promos will be analyzed partially and simultaneously on purchasing decisions. The form of research is quantitative research with an associative approach. Sampling was done through purposive sampling technique and used 100 respondents as samples. The primary data used was obtained by distributing questionnaires directly and through google form while secondary data was obtained through literature studies. The data analysis methods used are validity test, reliability test, classical assumption test, multiple linear regression analysis, and hypothesis testing. The results of the research conducted show that the affiliate marketing variable (X1) and the "special dates" promo (X2) partially and simultaneously have a significant effect on purchasing decisions. The coefficient of determination test shows that there is a fairly close relationship between affiliate marketing and "special dates" promos on purchasing decisions with an R value of 0.851. Through the adjusted R square value, it is also known that the affiliate marketing variable and the "special dates" promo contribute 71.9% to the purchasing decision variable, while the remaining 28.1% is influenced by other variables not discussed in this study